Determinan Agresivitas Pajak: Firm Size, Good Corporate Governance dan Financial Distress - Azizah, Jihan Nur; Sari, Shinta Permata (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Tax aggressiveness is related to tax planning actions taken by companies to reduce their tax obligations. This study aims to analyse the influence of firm size, institutional ownership, independent commissioners, and financial distress on tax aggressiveness at property and real estate sector companies listed on the Indonesia Stock Exchange in 2019-2023. This study uses a quantitative approach that is descriptive in nature with a purposive sampling method to determine the research sample. From 92 property and real estate sector companies, 15 companies are selected per year that met the predetermined criteria. Multiple linear regression analysis with the SPSS 26 program is used to test the hypothesis. The results of the analysis show that firm size, institutional ownership, and financial distress have an influence on tax aggressiveness, while independent commissioners have no influence on tax aggressiveness. This study is expected to help regulators in considering policies on corporate income tax burdens.